A method for top down preparation of chitosan nanoparticles and nanofibers. (6th March 2015) - Wijesena, Ruchira N.; Tissera, Nadeeka; Kannangara, Yasun Y.; Lin, Yuan; Amaratunga, Gehan A.J.; de Silva, K.M. Nalin
Highlights: Chitin nanofibers were extracted from crab shells and used as the initial material for chitosan nanostructure preparation. Chitin nanofibers were subjected to deacetylation to prepare chitosan. Prepared material is further ultrasonicated to prepare chitosan nanoparticles and nanofiber mixture. Nanoparticles were separated by simple gravity filtration method. Abstract: A method of top down preparation of chitosan nanoparticles and nanofibers is proposed. Chitin nanofibrils (chitin NFs) were prepared using ultrasonic assisted method from crab shells with an average diameter of 5 nm and the length less than 3 μm as analyzed by atomic force microscopy and transmission electron microscopy. These chitin nanofibers were used as the precursor material for the preparation of chitosan nanoparticles and nanofibers. The degree of deacetylation of these prepared chitosan nanostructures were found to be approximately 98%. In addition these chitosan nanostructures showed amorphous crystallinity. Transmission electron microscopic studies revealed that chitosan nanoparticles were roughly spherical in nature and had diameters less than 300 nm. These larger particles formed through self-assembly of much smaller 25 nm particles as evidenced by the TEM imaging. The diameter and the length of the chitosan nanofibers were found to be less than 100 nm and 3 μm respectively. It is envisaged that due to the cavitation effect, the deacetylated chitin nanofibers were broken down to small pieces to form seed particles. These seed particles can then be self-assembled to form larger chitosan nanoparticles.